Prediction of p-block-based ternary superconductors XC2H8 at low pressure - Izabela A. Wrona; Paweł Niegodajew; Yinwei Li; Artur P. Durajski (npj Computational Materials)
Abstract Achieving room-temperature superconductivity under ambient conditions is one of the most important goals in solid-state physics and material science. Recent discoveries of high-T c superconductivity in binary hydrides H3S and LaH10 at high pressures have focused the search for room-temperature superconductors on dense hydrides with conventional phonon-mediated pairing mechanisms. In this study, we predict a novel family of superconducting ternary hydrides under moderate compression, XC2H8 (X = Ga, In, Tl, Sn, Pb, Sb, Bi, Te, Po). Unlike H3S and LaH10, these new materials are stable at just around 20 GPa. Among the analyzed compounds, SbC2H8 exhibits the highest critical temperature of 73 K at a pressure of 100 GPa, which is attributed to its energetically favorable high-symmetry crystal structure ( $$Fm{\bar{3}}m$$ F m 3 ¯ m ), high density of states at the Fermi level (1.27 states/eV) and strong electron–phonon coupling constant (1.02). We expect that our findings provide crucial insights into achieving high-temperature superconductivity at moderate pressures and accelerate the progress of experimental research.